Glycolysis Paradigm Shift Dictates a Reevaluation of Glucose and Oxygen Metabolic Rates of Activated Neural Tissue - Schurr, Avital (Frontiers in Neuroscience, 2018)
In 1988 two seminal studies were published, both instigating controversy. One concluded that the energy needs of activated neural tissue are minimal, being fulfilled via the glycolytic pathway alone, a conclusion based on the observation that neural activation increased glucose consumption not accompanied by a corresponding increase in oxygen consumption (Fox et al.). The second demonstrated that neural tissue function can be supported exclusively by lactate as the energy substrate (Schurr et al.). While both studies continue to have their supporters and detractors, the present review attempts to clarify the issues responsible for the persistence of the controversies they have provoked and offer a possible rationalization. The concept that lactate, not pyruvate, is the end-product of glycolysis, both aerobically and anaerobically, and the real mitochondrial oxidative substrate has gained a greater acceptance over the years. The idea of glycolysis as the sole ATP supplier for neural activation (glucose → lactate + 2ATP) continues to be controversial. Lactate oxidative utilization by activated neural tissue could explain the mismatch between glucose and oxygen consumption and resolve the existing disagreements among users of imaging methods to measure the metabolic rates of the two energy metabolic substrates. The postulate that the energy necessary for active neural tissue is supplied by glycolysis alone stems from the original aerobic glycolysis paradigm. Accordingly, glucose consumption is accompanied by oxygen consumption at 1 to 6 ratio. Since Fox and colleagues observed only a minimal if nonexistent oxygen consumption compared to glucose consumption, their conclusion make sense. Nevertheless, considering a) the shift in the paradigm of glycolysis (glucose → lactate; lactate + O2 + mitochondria → pyruvate → TCA cycle → CO2 + H2O + 17ATP); b) that one mole of lactate oxidation requires only 50% of the amount of oxygen necessary for the oxidation of one mole of glucose and c) that lactate, as a mitochondrial substrate, is over eight times more efficient at ATP production than glucose as a glycolytic substrate, suggest that future studies of cerebral metabolic rates of activated neural tissue should include along with the measurements of CMRO2 and CMRglucose the measurement of CMRlactate.